Memahami Hubungan Religiusitas Dan Spiritualitas Di Era Milenial - Najoan , Denny (Educatio Christi, 2020)
The millennial era that continues the development of modernity has an impact on religious activities, which have an effect on the quality of spirituality. The current era shows that in terms of quantity and quality, there is a change in behavior in the spiritual life of the Christian young generation. This shows that competently there is an imbalance between doctrine and the value of religiosity with the spirituality of generations in the millennial era. This happens because of the lack of a clear understanding between the concepts of religiosity and spirituality in this era. Using the literature review method, which pays attention to various studies on religiosity and spirituality, this paper describes the relationship between religiosity and spirituality in the millennial era. According to some experts, religiosity and spirituality have a close relationship. Religiosity is a doctrinal activity to introduce each individual to religious teachings, rituals and rites, especially Christianity. While spirituality is an entity that exists in an individual, which is related to self-knowledge with God, and the existence of the self as part of the expression of belief in him. Thus the religious nature of the institutional, functional and substance, forming the spirituality of individuals to be able to implement religious values as part of the values in themselves. In the millennial era, the right approach is needed in carrying out religious activities. Activities that pay attention to millennial character and the technological devices used, are able to direct the generation spirituality to the introduction of good faith and social behavior in accordance with religious doctrine. Millennials still need religiosity to introduce themselves to the spiritual that directs them to a social life that is responsible and with integrity